2006
DOI: 10.1007/s10811-006-9105-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of plant growth regulators in micropropagation of Kappaphycus alvarezii (Doty) in airlift bioreactors

Abstract: The effects of plant growth regulators on callus induction rate and regeneration of K. alvarezii explants was evaluated. K. alvarezii calluses were induced in vitro with kinetin (K), 6-benzylaminopurine (B), 1-naphtalene acetic acid (N) and spermine (S). After 30 days, K. alvarezii explants produced filamentous calluses and isolated crystalline filaments growing from the medullar region and from cortical cells at the cut edge. The plant growth regulators 1-naphtalene acetic acid (1 mg L −1 ) and 6-benzylaminop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…Species of Grateloupia showed the highest regeneration potential, which could be increased by the addition of plant growth regulators (auxins and/ or cytokinins), as reported for Grateloupia dichotoma by Yokoya & Handro (1996. For other species of Gigartinales, regeneration from callus was found to be stimulated by PGR in Solieria filiformis (Yokoya & Handro, 2002), Hypnea musciformis (Yokoya et al, 2003) and Kappaphycus alvarezii (Muñoz et al, 2006). However, the presence of PGR was facultative for the last two species, as reported by Bravin et al (2006) and Reddy et al (2003), respectively.…”
Section: Plant Growth Regulators (Pgr) In Rhodophytamentioning
confidence: 69%
“…Species of Grateloupia showed the highest regeneration potential, which could be increased by the addition of plant growth regulators (auxins and/ or cytokinins), as reported for Grateloupia dichotoma by Yokoya & Handro (1996. For other species of Gigartinales, regeneration from callus was found to be stimulated by PGR in Solieria filiformis (Yokoya & Handro, 2002), Hypnea musciformis (Yokoya et al, 2003) and Kappaphycus alvarezii (Muñoz et al, 2006). However, the presence of PGR was facultative for the last two species, as reported by Bravin et al (2006) and Reddy et al (2003), respectively.…”
Section: Plant Growth Regulators (Pgr) In Rhodophytamentioning
confidence: 69%
“…Yokoya and Handro (2002) and Muñoz et al (2006), it has not yet been shown that seaweeds are able to take up cytokinins from the growth medium. However, the numerous examples of the positive effects that applied cytokinins have on seaweeds grown in culture suggest that this is likely and thus cytokinins occurring in seawater may influence the growth of seaweeds.…”
Section: Marine Environmentmentioning
confidence: 99%
“…The advantage of Kappaphycus is that techniques for its micro-propagation have long been worked for efficient and rapid plantlet regeneration (Dawes and Koch 1991;Dawes et al 1993;Muñoz et al 2006). Callus formation can be observed after 15 days of culture (Hayashi et al 2008b) and a new plant can be micro-propagated in about 30 days (Hurtado and Biter 2007).…”
Section: Discussionmentioning
confidence: 99%